Pelatihan Pembuatan Konten Instagram Menggunakan Aplikasi Canva untuk Staf dan Guru Yayasan An-Nur - Pamela, Apsari Wiba; Yulrifanto, Rifky; Ningrum, Nina Nursetia (Universitas Dinamika, 2025)
Digitalization has changed the communication paradigm of educational institutions, expanding the role of social media as a strategic tool to expand reach and increase interaction with the community. Community service activities which include training in creating Instagram using the Canva application for content staff and teachers of the An-Nur Foundation in the context of digitalization which is spreading to the world of education. This training aims to strengthen the skills of staff and teachers at the An-Nur Foundation in creating interesting and relevant visual content, which can support the foundation's efforts in promoting its educational mission so that it is more widely known. The training method includes presentation of material and direct practice sessions using the Canva application which is tailored to the needs of the An-Nur Foundation's Instagram content. By using the Canva application as the main tool, training participants are encouraged to adopt easy-to-use technology to manage Instagram content effectively. The evaluation results show an increase in participants' competence in utilizing social media as an effective and strategic means of communication. Based on the posttest results, 90% of participants understood the material presented and 75% of participants could apply the training results by using the Canva application independently to create Instagram content.